Using dietary metabarcoding analyses to characterise waterbirds–agriculture interactions. Issue 11 (26th September 2022) - Corriveau, Amélie; Klaassen, Marcel; Garnett, Stephen T.; Kaestli, Mirjam; Power, Matthew W.; Mousavi‐Derazmahalleh, Mahsa; Coghlan, Megan L.; Christian, Keith; Bunce, Michael; Campbell, Hamish A.
Abstract: Globally, the use of agricultural fields by waterbirds has increased, resulting in conflicts with farmers. Designing effective management strategies to resolve these conflicts requires understanding the species' resource use. Dietary analyses can shed light on the extent of consumption of agricultural crops and surrounding natural resources, as well as the potential relationship between diet and an individual's body condition and ultimately its fitness. We examined the dietary composition of the tropical magpie goose Anseranas semipalmata, seasonally utilising a mixed natural‐agricultural landscape of northern Australia. We used DNA metabarcoding of intestinal contents from hunted geese to reconstruct individual diets and evaluated body condition from morphometric measurements. We compared the relative contribution of agricultural and natural foods to dietary composition, and investigated how this contribution varied spatially, temporally and among individuals that differed in body condition. We found that geese consumed both agricultural and naturally occurring plants assigned to at least 35 taxa. The most frequent and abundant taxa belonged to three families: Poaceae (grasses), Cyperaceae (sedges) and Anacardiaceae (mangoes). Dietary composition varied substantially among sampling sites and over time but not with body condition of geese. Synthesis and applications . We used a novel approach to investigate the diet of a waterbird perceived as problematic across an agricultural landscape in tropical Australia. We showed that individuals forage opportunistically, and that agricultural crops, while eaten, may not represent an essential part of geese diet across the study region. The knowledge acquired provides new insights into the species' foraging ecology offering clear alternatives for mitigating goose–agriculture interactions. Providing disturbance‐free alternative foraging areas or minimising the attractiveness of targeted agricultural fields (e.g. shorter grass, alternative ground cover) may alleviate crop consumption while benefiting the species' long‐term conservation. While also highlighting the limitations of DNA metabarcoding, our dietary study emphasises the potential of this methodology to improve our understanding of crop damage by wildlife, allowing effective evaluation of management requirements. Abstract : We used a novel approach to investigate the diet of a waterbird perceived as problematic across an agricultural landscape in tropical Australia. We showed that individuals forage opportunistically, and that agricultural crops, while eaten, may not represent an essential part of geese diet across the study region. The knowledge acquired provides new insights into the species' foraging ecology offering clear alternatives for mitigating goose–agriculture interactions. Providing disturbance‐free alternative foraging areas or minimising the attractiveness of targeted agricultural fields (e.g. shorter grass, alternative ground cover) may alleviate crop consumption while benefiting the species' long‐term conservation. While also highlighting the limitations of DNA metabarcoding, our dietary study emphasises the potential of this methodology to improve our understanding of crop damage by wildlife, allowing effective evaluation of management requirements. Résumé: L'utilisation des milieux agricoles par les oiseaux aquatiques sauvages a augmenté de façon considérable à travers le monde entraînant des conflits avec les agriculteurs. Afin de concevoir des stratégies de gestion efficaces pour résoudre ces conflits, il est nécessaire de comprendre comment l'espèce utilise les ressources environnantes. L'analyse du régime alimentaire peut permettre de comparer la consommation de cultures agricoles et celle des ressources naturelles environnantes, ainsi que d'évaluer la relation potentielle entre l'alimentation et la condition physique d'un individu et, finalement, sa valeur sélective. Nous avons examiné la composition du régime alimentaire de l'oie semi‐palmée Anseranas semipalmata tropicale, qui utilise de façon saisonnière un paysage mixte naturel‐agricole du nord de l'Australie. Nous avons reconstitué le régime alimentaire d'individus en utilisant le métabarcodage d'ADN du contenu intestinal d'oies chassées et avons évalué leur condition physique à partir de mesures morphométriques. Nous avons comparé la contribution relative des cultures agricoles et ressources naturelles au régime alimentaire, puis nous avons examiné comment cette contribution variait de façon spatiale, temporelle, ainsi qu'entre individus de différentes conditions physiques. Les résultats de notre étude indiquent que les oies consommaient des plantes agricoles et naturelles attribuées à au moins 35 groupes taxonomiques. Les taxons les plus fréquents et abondants appartenaient à trois familles: Poaceae (graminées), Cyperaceae (carex) et Anacardiaceae (mangues). La composition du régime alimentaire variait considérablement entre les sites d'échantillonnage et au fil du temps, mais pas avec la condition physique des individus. Synthèse et applications . Nous avons utilisé une nouvelle approche pour étudier le régime alimentaire d'un oiseau aquatique perçu comme problématique dans un paysage agricole tropical d'Australie. Nous avons observé que les individus se nourrissaient de manière opportuniste et que, bien que consommées, les cultures agricoles ne représentaient pas nécessairement une partie essentielle du régime alimentaire des oies dans la région d'étude. Les connaissances acquises fournissent de nouvelles informations sur l'écologie alimentaire de l'espèce et offrent des solutions alternatives pour atténuer les interactions entre les oies et l'agriculture. La création de zones d'alimentation alternatives sans perturbation ou la réduction de l'attrait des champs agricoles ciblés (par exemple, herbe plus courte, plantes non‐comestibles) pourraient réduire la consommation des cultures agricoles tout en favorisant la conservation de l'espèce à long terme. Bien que nous soulignions certaines limites du métabarcodage d'ADN, notre étude démontre le potentiel de cette méthodologie pour mieux comprendre les dommages aux cultures agricoles causés par la faune afin d'évaluer les besoins de gestion.